7-Hydroxycoumarin Elicit Anti-Angiogenic Effects Through Cellular Apoptosis in Developing Embryos of Zebrafish (Danio Rerio) - Anegundi, Narshimamurthy; Pancharatna, Katti (European Scientific Journal, ESJ, 2017)
Derivatives of coumarin have diverse biological activities and pharmacological significance. In this study we made an attempt to test one of the hydroxy derivative i.e. 7-hydroxycoumarin (7HC) for its anti-angiogenic potential using embryonic angiogenesis of zebrafish (Danio rerio) as biological model. Developing embryos of D. rerio were cultured in media containing one of the grade (1 mM or 2 mM or 3 mM or 4 mM or 5 mM) of concentration of 7HC from gastrula stage ( 6 hrs post fertilization - hpf) until completion of embryonic development and hatching (72 hpf). Developmental trajectory of each post hatched larva was traced for two weeks. Angiogenesis and patterning of major blood vessels occurred in zebrafish embryos/ larvae between 24 - 72 hpf in controls. Exposure to 7HC resulted in an impairment in patterning of inter segmental vessels (ISVs) dorsal aorta (DA), dorsal longitudinal anastomotic vessel (DLAV), posterior cardinal vein (PCV), and common cardinal veins (CCVs) accompanied by increased site specific cellular apoptosis, declined heart rates in a dosedependent manner. 7HC manifest anti-angiogenic effects mediated/ induced through cellular apoptosis, hence may deserve attention and consideration as tumour angiogenesis suppressors in malignancy therapeutics.